An evaluative survey of public libraries in Batangas - Catilo, Marissa R. 1969- (1996)
The descriptive survey method was used. Data and relevant information were obtained by means of questionnaire and personal interviews.
The results of the study point to the fact that the public libraries in Batangas have failed to contribute meaningfully to the dissemmination of knowledge and information to library users. The noble purpose of a public library could easily be achieved if improvements are initiated with the financial and administrative support from the municipal government.
The study revealed that public libraries in Batangas are sub-standard or below standard. The book collections are very inadequate. There are no supplementary reading materials and many books are already worn-out and outdated. most of the books in the collection are textbooks. Audiovisual materials and equipment are not available in any of public libraries in Batangas. The above mentioned findings deemed to be rooted in two basic problems: lack of financial support on the part of government officials and lack of professional expertise an the part of library personnel and other staff members. However, it's but proper to note that librarians and other staff members expressed their willingness to improve their craft given the opportunity.
This study was conducted to determine the extent of compliance of public libraries in Batangas to the 1988 PLAI Proposed Minimum Standards for Public Libraries.
Thesis (M.L.S.)--University of the Philippines, Diliman.
Typescript.
Vita.
Keywords: Public libraries -- Standards. -- Philippines -- Batangas